2021
DOI: 10.1044/2021_aja-20-00228
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Patient Narratives to Enhance Audiological Care and Clinical Research Outcomes

Abstract: Purpose The engagement of patients as key stakeholders in their experience of care processes is a critical component of quality improvement efforts for both clinical care and translational research. Increasingly, health care systems are soliciting input from patients on care processes and experiences through surveys, patient interviews, and patient video narratives. The purpose of this viewpoint article is twofold: (a) to describe the increasing role of patient narratives about their experiences wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The variation in the audiologists’ perspectives on when ototoxicity should be monitored may reflect the need to expand and refine existing guidance on OtoM protocols [ 26 , 32 ]. Patient narratives [ 46 ] and data from a small clinical trial [ 34 ] indicate that patients value being able to access hearing healthcare during treatment with an ototoxic therapy and will follow-up to obtain new hearing aids or hearing aid adjustments. However, the clinical trial results revealed significant barriers to patients accessing OtoM in VA and suggest that a screening approach may help overcome some of these barriers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variation in the audiologists’ perspectives on when ototoxicity should be monitored may reflect the need to expand and refine existing guidance on OtoM protocols [ 26 , 32 ]. Patient narratives [ 46 ] and data from a small clinical trial [ 34 ] indicate that patients value being able to access hearing healthcare during treatment with an ototoxic therapy and will follow-up to obtain new hearing aids or hearing aid adjustments. However, the clinical trial results revealed significant barriers to patients accessing OtoM in VA and suggest that a screening approach may help overcome some of these barriers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This research also suggests that parent experiences, narratives, and perspectives can be undervalued as clinicians work with families. As families have been shown to be a crucial aspect of healthcare (Martin et al, 2021), one possible solution to improving this gap in hearing healthcare includes providing a familycentered care approach to clinical care. Family-centered care is an approach to health care in which the patient, family, and provider have a mutually beneficial partnership as they navigate health decisions together (Kuo et al, 2012).…”
Section: Family-centered Carementioning
confidence: 99%
“…This example, along with findings from other familycentered care research (Nickbakht et al, 2021;Schmulian & Lind, 2019;Shulman et al, 2010), highlights the importance of clinicians listening to parents about their needs, perspectives and wants as they address each family and the child's healthcare. Recall, research on incorporating patient narratives in health care (Clark et al, 2021) demonstrated patient benefits when providers take time to listen to the patient's/family's reactions and perspectives. Thus, if pediatric hearing health care providers make sure to check in with families regarding their feelings following a HL diagnosis (e.g., via open-ended questions such as "How do you feel about this information?…”
Section: Provider Support As Parents Encounter the Reality Of Pediatr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Uncovering parents’ experiences is crucial to the success of healthcare and treatment clinicians provide families, thus identifying potential improvements in patient outcomes (Russ et al 2004; Kreuter et al 2007; Smith & Sparkes 2008; Frost et al 2010). For example, Clark et al (2021) found patient narratives benefit clinical work by building provider awareness to the unique and individual situation of each patient and family. Such findings could be foundational in improving pediatric clinical care by revealing what resources and support parents need, or reinforcing what current practices have worked well in the clinician-parent relationship, such as family-centered care.…”
Section: Parents’ Experiences With Their Infants’ Hearing-loss Diagnosesmentioning
confidence: 99%